Production of geopolymer concrete by utilizing volcanic pumice dust. (June 2022) - Zeyad, Abdullah M.; Magbool, Hassan M.; Tayeh, Bassam A.; Garcez de Azevedo, Afonso Rangel; Abutaleb, Ahmed; Hussain, Qudeer
Abstract: The urgent need to find green alternatives to cement concrete in order to reduce the consumption of fossil fuels and non-renewable resources that are used to produce cement. This research aims to study the possibility of using volcanic pumice dust (VPD) waste with cement kiln dust (CKD) or Ordinary Portland cement (OPC) to produce alkaline activated green concrete (HAC). VPD was used to improve the mechanical performance, strength, and engineering properties of HAC. CKD and OPC were used as a partial replacement for VPD in different proportions of 0, 5%, 10%, 20%, and 30% by weight. Na2 SiO3 and NaOH were used as alkaline activator solutions to realize the alkaline reaction process in geopolymer paste. Workability, compressive strength, and engineering properties, such as bulk density, porosity, and water absorption, were studied. Results of this research indicated that increasing the replacement rates of CKD or OPC decreased slump flow but increased the strength of HAC and enhanced the values of its engineering properties. Geopolymer concrete with OPC and CKD as partial replacement of 30% by weight of VPD achieved an increase of 23% and 8%, respectively, in compressive strength at a test age of 90 days. Meanwhile, 20% VPD replacement by CKD achieved 11% higher compressive strength for the VPD–CKD samples compared with the control mixture. In addition, water absorption rate decreased by 25% and 20%, respectively, compared with the control samples.